2015
DOI: 10.1016/j.solener.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the clear-sky intensity distribution using a sky imager

Abstract: International audienceThis paper introduces a new empirical formulation of the clear-sky intensity distribution based on images acquired with a sky imager developed at the PROMES-CNRS laboratory (Perpignan, France). Both the formulation and image processing methodology are detailed and stand for key steps in the development of a high quality cloud detection algorithm. The work presented in this paper is a part of a research project which aims at improving solar plant control procedures using direct normal irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 46 publications
0
23
0
1
Order By: Relevance
“…The HDR image generation is briefly described in the following section. The clear-sky images are generated via the methodology detailed by Chauvin et al in [7]. Secondly, the continuous forecasting scheme introduced by Bernecker et al could be adapted to our application.…”
Section: Selected Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The HDR image generation is briefly described in the following section. The clear-sky images are generated via the methodology detailed by Chauvin et al in [7]. Secondly, the continuous forecasting scheme introduced by Bernecker et al could be adapted to our application.…”
Section: Selected Approachmentioning
confidence: 99%
“…the 3-D rotation matrix that align the camera with the zenith, is obtained by comparing the position of the Sun as detected on the image with the real one calculated using the SG2 algorithm [19]. More details about the calibration process can be found in [7]. Once the camera is calibrated, it is possible to interpolate the pixels' values from the sensor coordinate system to the world coordinate system, where the zenith corresponds to the center of the image and the top of the image faces north.…”
Section: Image Featurementioning
confidence: 99%
See 1 more Smart Citation
“…• the analysis of power spectra and non-linear characteristics of PV power and solar irradiance time series [16,17,32,35,42,43,48,[64][65][66][67][68], • the comparison of power fluctuations from specific PV plants with corresponding irradiance measurements [25,43,57,69], • the characterization of power variability as a function of PV plant size [13,25,36,44], • the assessment of the effects of partial shadowing on performance reduction from single modules to entire PV systems [51,[70][71][72], • the development of methods to infer irradiance and PV power estimates from whole sky images [47,[73][74][75][76][77][78][79][80][81], • the proposition of classification schemes and measures to quantify variability [25,38,39,[82][83][84][85][86][87], • the estimation of spatial smoothing, including correlation structures and decorrelation length scales of irradiance and PV power, as well as their increments…”
Section: Introductionmentioning
confidence: 99%
“…Ghonima et al (2012) and Shields et al (2013) give rich and interesting reviews of sky imager systems and their applications. Several algorithms have now been proposed that enable us to retrieve an estimation of cloud cover (e.g., Long and DeLuisi, 1998;Li et al, 2011;Ghonima et al, 2012;Martinis et al, 2013;Silva and Echer, 2013;Cazorla et al, 2015;Kim et al, 2016;Krinitskiy and Sinitsyn, 2016) or solar irradiance (Pfister et al, 2003;Chu et al, 2014;Chauvin et al, 2015;Kurtz and Kleissl, 2017), to classify the type of observed clouds (e.g., Heinle et al, 2010;Kazantzidis et al, 2012;Xia et al, 2015;Gan et al, 2017), or to track them (Peng et al, 2015;Cheng, 2017;Richardson et al, 2017). Sky imagers have also been specifically used for the detection of cirrus or thin clouds (Li et al, 2012) and contrail studies (Schumann et al, 2013).…”
mentioning
confidence: 99%